ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI KENTANG DI DESA BUNTU KECAMATAN KEJAJAR KABUPATEN WONOSOBO - Anggraeni, Rini; Rahul Sebayang; Kadarso; Cungki Kusdardjito (Jurnal Pertanian Agros, 2026)
This study aims to analyze the income and economic feasibility of potato farming in Buntu Village. The study used a quantitative descriptive method involving 76 farmers selected using simple random sampling. Data were collected through interviews, questionnaires, and observations, then analyzed using calculations of production costs, revenue, income, profit, and R/C and B/C ratios. The results showed an average income of Rp 37,989,605/season/farm, or Rp 108,541,729/ha. Explicit income reached Rp 21,276,168/season/farm, or Rp 60,789,052/ha, but economic profit was only Rp 2,100,642/season/farm, or Rp 6,001,834/ha. An R/C ratio of 1.06 indicates technical feasibility, but a B/C value of 0.06 indicates a very low profit margin and a high level of economic vulnerability. Key-words: Income, Feasibility, Potato farming.